ВИЗНАЧЕННЯ АНТИОКСИДАНТНОЇ АКТИВНОСТІ ЗАБАРВЛЕНИХ РОСЛИННИХ ЕКСТРАКТІВ IN VITRO - Lamazian, H. R.; Sytnyk, I. M.; Chernovol, P. A.; Chekman, I. S.; Khaitovych, M. V. (Фармацевтичний часопис, 2016)
DETERMINATION OF ANTIOXIDANT ACTIVITY IN COLOR PLANT EXTRACTS IN VITRO G.R. Lamazian, I.M. Sytnik, P.A. Chernovol, I.S. Chekman, M.V. Khaitovych Bogomolets National Medical University, Kyiv Introduction. To date, the relationship between free radical oxidation and the development of most pathological processes - endocrinology and cardiovascular diseases is proved. Modern living conditions, the negative impact of environmental factors, emotional stresses, genetic factors - all these are a prerequisite for initiating redox balance disturbances in the body. A key role in this regard belongs to reactive oxygen species (ROS), which cause development of oxidative stress (OS). Recently, the antioxidant properties of medicinal plants (MP) in the prevention and correction of the OS are actively studied. It is commonly known that MP is a source of polyphenolic compounds - powerful natural antioxidants that inhibit free radical oxidation chain reaction through inhibition of oxidative enzymes, the formation of metal chelates or neutralization of radicals. The aim of this work was to study the antioxidant activity (AOA) of Hypericum perforatum (L.) and Citrullus colocynthis (L.) Shrad. extracts on the model of superoxide radical inhibition in vitro. Investigation methods. Determination of AOA was carried out spectrophotometrically according to the change in absorbance of studied extracts in a model test system of adrenaline autoxidation in an alkaline medium at a wavelength of 340 nm. Assessment of AOA was conducted by the degree of inhibition of superoxide radical, taking into account the impact of extracts’ color that absorbs certain wavelength in the visible spectrum. Results and discussion. Investigated extracts show high AOA in a range of all concentrations, preventing the formation of superoxide radical in vitro. It was somewhat higher in H. perforatum versus C. colocynthis. It should be noted that the AOA of extracts depends on their concentration. The highest value of AOA for H. perforatum (95,77%) is detected at a concentration of 0.5 mg/ml. C. colocynthis showed maximum AOA (88.62%) at a concentration of 0,5˟10-3 mg/ml. Values of absorbance after ten minutes exposure indicate that with time the AOA of extracts decreases due to their multi-component composition and interinfluence of biologically active substances, which can be both antagonists and synergists. It is known that the antioxidant effect of MP is achieved due to nonenzymatic molecules represented mainly by polyphenolic compounds – flavonoids, phenolcarbonic acids, catechins, stilbenes etc. Activation of cell protective mechanisms by plants polyphenols significantly reduces the manifestations of the OS. Thus, a number of epidemiological and experimental studies indicate that regular action of natural polyphenols improves the quality of patients’ lives with diabetes, Alzheimer's disease, hypertension, metabolic syndrome. Conclusions. 1. In was established that the plant extracts of H. perforatum (L.) and C. colocynthis (L.) Shrad. possess AOA in a range of all concentrations. 2. Extracts activity depends on the concentration. The highest value of AOA for H. perforatum (95,77%) is detected at a concentration of 0.5 mg/ml and for C. colocynthis (88.62%) - at a concentration of 0,5˟10-3 mg/ml. 3. The decrease in AOA with time (10 minutes exposure) was revealed, which may be due to the interinfluence of biologically active substances in extracts. References 1. Significance of antioxidant potential of plants and its relevance to therapeutic applications / D. M. Kasote, S. S. Katyare, M. V. Hegde [et al.] // International Journal of Biological Sciences. – 2015. – Vol. 11, № 8. – P. 982–991. 2. Chemical and molecular mechanisms of antioxidants: experimental approaches and model systems/ Jian-Ming Lüa, P. H. Lin, Q. Yao [at al.] // J Cell Mol Med. – 2010. – Vol.14, № 4. – P.840–860. 3. Upadhyay S. Role of polyphenols and other phytochemicals on molecular signaling / S. Upadhyay, M. Dixit // Oxidative Medicine and Cellular Longevity. – 2015. – Vol. 2015. – [Elektronnyy resurs].– Rezhym dostupu: http://dx.doi.org/10.1155/2015/504253 4. Praktykum po farmakohnozyy: Ucheb. posobye dlya stud. vuzov / [Kovalev V. N., Popova N. V.y dr.]; pod obshch. red. V. N. Kovaleva.— KH.: Yzd-vo NFaU; Zolotye stranytsy, 2003.— S. 64-65. 5. Tykhonov A. Y. Tekhnolohyya lekarstv: Ucheb. dlya farmats. vuzov y fak.: Per. s ukr. / A. Y. Tykhonov, T. H. Yarnykh. — KH.: Yzd-vo NFaU; Zolotye stranytsy, 2002. – S. 331-337. 6. Morhuntsova S.A. Antyoksydantna aktyvnistʹ S-zamishchenykh khinazolinu v umovakh inhibuvannya superoksydradykala in vitro / S.A. Morhuntsova, I.F.Byelenichev // Visnyk Zaporizʹkoho natsionalʹnoho universytetu. – 2009. – № 1. –S.161–165. 7. Impact of origin and biological source on chemical composition, anticholinesterase and antioxidant properties of some St. Johnʺs Wort species (Hypericum spp., Hypericaceae) from the central Balkans / B. Božin, N. Kladar, N. Grujić [et al.] // Molecules. – 2013. – № 18. – P.11733–11750. 8. Syrota T.V. Novyy podkhod v yssledovanyy reaktsyy avtookyslenyya adrenalyna: vozmozhnostʹ polyarohrafycheskoho opredelenyya aktyvnosty superoksyddysmutazy y antyoksydantnykh svoystv razlychnykh preparatov / Syrota T.V. // Byomedytsynskaya khymyya. – 2012. – T. 58, vyp. 1. – S. 77–87. 9. Jayaraman R. Evaluation of Citrullus colocynthis fruits on in vitro antioxidant activity and in vivo DEN/PB induced hepatotoxicity / R. Jayaraman, Christina A.J.M. // IJARNP. – 2013. – Vol. 6, № 1. – P. 1–9. 10. Flavone c-glycosides and cucurbitacin glycosides from citrullus colocynthis / A. Delazar, S. Gibbons, A. R. Kosari [et al.] // DARU. – 2006. – Vol.14, № 3. – P. 109–114. 11. Igwenyi I. O. Phytochemical Analysis and Vitamin Composition of Irvigna Gabonesis and Citrullus Colocynthis / I. O. Igwenyi // IOSR-JPBS. – 2014. – Vol. 9, № 3. – P. 37–40. 12. Pro- ta antyoksydantna systemy i patolohichni protsesy v orhanizmi lyudyny / O.H. Reznikov, O.M. Polumbryk, YA.H. Balʹon [ta in.] // Visn. NAN Ukrayiny. – 2014. – № 10. – S.17–29. 13. Polyphenol stilbenes: molecular mechanisms of defence against o xidative stress and aging-related diseases / M. Reinisalo, A.Kårlund, A. Koskela [et al.] // Oxidative Medicine and Cellular Longevity. – 2015. – Vol. 2015. –– [Elektronnyy resurs].– Rezhym dostupu: http://dx.doi.org/10.1155/2015/340520